REMOVAL OF DISSOLVED SALTS USING CARBON BASED MIXED MATRIX MEMBRANES - QADIR, DANIAL (2018)
Membrane technology had played an influential role to meet the ever increasing global water demands. Recent advances in membrane technology have focused on reducing the tradeoff between rejection and flux at cheaper costs. The main objective of this study is to synthesize and analyze the performance of polyethersulfone (PES)/carbon molecular sieve (CMS) based mixed matrix membranes (MMM) for the removal of dissolved salts from aqueous solutions.